Intravascular Large Cell non-Hodgkin Lymphoma in Subacute-Chronic Subdural Hematoma: a case report (Research, Society and Development, 2022)
Introduction: Intravascular lymphoma (IVL) is a rare subtype of non-Hodgkin extranodal lymphoma with characterized by a positive CD20 B cell proliferation in small lumens and medium-sized blood vessels, except veins and large arteries. Blood vessels in the central nervous system (CNS) and the skin is most often affected. These tumors usually occur in older adults and aggressive. Methodology: Descriptive study of the case report type, whose data were obtained from the patient’s medical record and has received the patient's consent to be published. Case presentation: This paper reports a 63-year-old man, who suffered Parkinson disease and neurological symptoms for 6 months. From imaging, there is a chronic subacute subdural hematoma in the right frontotemporoparietal area. Operation performed, histopathological examination of the tissue with Hematoxylin-Eosin staining and immunohistochemical examination confirmed diagnosis Intravascular Large Cell non-Hodgkin Lymphoma (IVLCL) type B-cell CD20 (+) in subacute-chronic subdural hematoma (SDH). Discussion: This tumor is characterized by selective growth of lymphoma cells within the lumen of blood vessels, particularly capillaries, and with the exception of the larger arteries and veins, occurred in adults, with a median age of 67 years. Sixty five percent show neurological symptoms with rapidly progressive cognitive dysfunction or subacute dementia. The cause of chronic SDH in this patient is unknown, but it can occur due to increasing age, brain atrophy, and enlargement of the subdural space, relatively minor trauma. Conclusion: This lymphoma is aggressive with a poor prognosis but a chemotherapy regimen with rituximab significantly improves the clinical outcome of this patient, with an overall survival of 3 years 60-81%.